'Lasst uns zur Freundlichkeit Gehen': A Saying Misattributed to Papias of Hierapolis - Carlson, Stephen C. (The journal of theological studies, 2018)
Theodor Zahn mentions a saying, 'Lasst uns zur Freundlichkeit gehen', attributed to Papias of Hierapolis in the works of C. F. D. Schubart (1739-91) and other German devotional writers. Zahn knew that it did not belong to Papias but nonetheless asked his fellow scholars where it came from. This article traces the convoluted history of this saying back to its origin in the early modern period.